Control of post-acidification and shelf-life prediction of apple juice fermented by lactobacillus. (September 2022) - Bai, Xue; Han, Mengzhen; Yue, Tianli; Gao, Zhenpeng
Abstract: To control the post-acidification caused by the continued fermentation of Lactobacillus in fermented apple juice (FAJ) during cold storage and establish a shelf-life prediction model of the post-acidification process, the effects of nisin and ε-polylysine on the physicochemical and microbiological properties of FAJ during cold storage were evaluated. In addition, quality indexes and shelf-life prediction models of fermented apple juice with the addition of nisin (FAJN) were established and verified. The post-acidification control effect of 40 mg/L nisin was determined to be optimal. Furthermore, deterioration of quality indicators of FAJ treated with 40 mg/L nisin was significantly controlled, and the shelf-life was prolonged compared with FAJ. Prediction models of L*, a*, b*, ΔE, viable cell count, and the stability coefficient of FAJN were established and verified, and a shelf-life prediction model was established with the number of viable bacteria as the prediction indicator. Relative errors between the predicted and measured values of each model were within ±10%, indicating that the models could predict changes in each index and the shelf-life of FAJN when stored at 4 °C and 25 °C. Highlights: Nisin (40 mg/L) can be used to control the post-acidification of FAJ. The shelf-life of FAJN was extended by 7 days compared with FAJ. The models could predict changes in each index and the shelf-life of FAJN.